Pengaruh Penerapan Sistem Informasi Pemerintah Daerah (SIPD), Transparansi Anggaran, dan Akuntabilitas Pengelolaan Keuangan Terhadap Kualitas Pelaporan Keuangan Pemerintah Kabupaten Siak - Afrizal, Donny Tirtana; Armaini, Rosy; Hasibuan, Rahmawaty (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The quality of local government financial reporting remains a concern because an Unqualified Opinion (WTP) does not fully reflect the absence of internal control system (SPI) weaknesses or non-compliance with regulations. This situation is evident in the Siak Regency Government; despite receiving an Unqualified Opinion for over a decade, Audit Result Reports (LHP) from the Audit Board of the Republic of Indonesia (BPK) indicate that the government still faces SPI weaknesses and material non-compliance. This study aims to analyze the influence of the Local Government Information System (SIPD), budget transparency, and financial management accountability on the quality of financial reporting. A quantitative approach was employed, utilizing primary data collected via questionnaires from 63 respondents, comprising Budget User Proxies (KPA), treasurers, and finance staff. Data analysis was conducted using multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results indicate that SIPD, budget transparency, and accountability simultaneously have a significant effect on the quality of financial reporting. Individually, SIPD and accountability have a positive and significant effect, whereas budget transparency does not have a significant effect. Accountability emerged as the most dominant variable. The research model explains 56.2% of the variation in financial reporting quality